POTENSI PEMBELAJARAN MANUSIA : PERSPEKTIF NEUROSAINS DAN ISLAM - Himayatul Izzati (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2021)
The verses of the Al-Quran which talk about the potential of learning and neuroscience, describe the activity of the mind and the brain as a learning instrument to understand, study and analyze, these signals can be traced through key terminology related to human brain activity. The terms tafakkur, tadabbur, ta'aqqul are theological foundations that describe the potential for human learning in a Neouroscience perspective. The brain is the center of human intelligence which controls the entire nervous system in capturing learning activities. with the power of the human brain can find various things that can facilitate human life. Cues of potential learning by maximizing brain nerve function (Neuroscience) can be traced to, QS Asy-Shams Verses 7-9, QS. An-Nahl 78, QS Ar-Rum 8, QS Al-Baqarah 219 and QS. Muhammad 24. The potential for human learning that is implemented in Islamic education, must develop a variety of potentials, so that the implementation of Islamic education can maximize the development of a comprehensive potential, such as Tarbiyah Imaniyah, Khuluqiyah, Tarbiyah, Jismiyah, Tarbiyah Aqliyah, Nafsiyah Ijtima'iyah. By maximizing the development of the potential, it will produce quality Islamic education output.